Pengaruh Kepercayaan Nasabah Terhadap Minat Menabung di Bank Syariah - Novianto, Satrio; Nisa, Fauzatul Laily (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study examines the impact of customer trust on savings interest in Shariah banks. Shariah banks, which operate based on Islamic principles, have gained popularity globally due to their unique financial products and services. However, customer trust remains a crucial factor in determining the success of these banks. This research aims to investigate the relationship between customer trust and savings interest in Shariah banks, with the goal of providing insights for these institutions to enhance customer loyalty and retention. The study employs a survey methodology and uses a sample of Shariah bank customers. The results indicate that customer trust significantly influences savings interest in Shariah banks, suggesting that banks should focus on building trust with their customers to increase savings interest.